2015
DOI: 10.1051/m2an/2014032
|View full text |Cite
|
Sign up to set email alerts
|

An analysis of HDG methods for convection-dominated diffusion problems

Abstract: Abstract. We present the first a priori error analysis of the h-version of the hybridizable discontinuous Galkerin (HDG) methods applied to convection-dominated diffusion problems. We show that, when using polynomials of degree no greater than k, the L 2 -error of the scalar variable converges with order k + 1/2 on general conforming quasi-uniform simplicial meshes, just as for conventional DG methods. We also show that the method achieves the optimal L 2 -convergence order of k + 1 on special meshes. Moreover… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
71
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 61 publications
(71 citation statements)
references
References 41 publications
(88 reference statements)
0
71
0
Order By: Relevance
“…These boundary conditions were derived after assuming the region L w < z < L d to be uncharged and at local quasi-thermal equilibrium [18]; furthermore, a bias voltage V ext was applied at the plane z = L d . Solution of this system of equations was undertaken using the HDG scheme [46,25,45], in which all the z-dependent variables have to be discretized using discontinuous finite elements in a space of piecewise polynomials of a fixed degree. The full discretized system was solved for n(z), p(z), and φ(z), using the Newton-Raphson method [43].…”
Section: Electrical Theorymentioning
confidence: 99%
“…These boundary conditions were derived after assuming the region L w < z < L d to be uncharged and at local quasi-thermal equilibrium [18]; furthermore, a bias voltage V ext was applied at the plane z = L d . Solution of this system of equations was undertaken using the HDG scheme [46,25,45], in which all the z-dependent variables have to be discretized using discontinuous finite elements in a space of piecewise polynomials of a fixed degree. The full discretized system was solved for n(z), p(z), and φ(z), using the Newton-Raphson method [43].…”
Section: Electrical Theorymentioning
confidence: 99%
“…The nonlinear Shockley-Read-Hall, Auger, and radiative terms are included to model electron-hole recombination [1,2]. A hybridizable discontinuous Galerkin (HDG) method [10,11,12,13] is developed, and the Newton-Raphson method [14] is used to find a solution of the resulting nonlinear system.…”
Section: Introductionmentioning
confidence: 99%
“…By a similar argument used in this paper, we can show that the HDG method for the convection dominated diffusion equation (1.5) is well defined for any > 0. Under the same assumption of β in [10], it can be shown that u h − u ≤ Ch k+1/2 u k+2, , where the constant C is independent of .…”
Section: Introductionmentioning
confidence: 98%
“…Namely, we can decompose the stabilization function used in the numerical flux (1.3e) into diffusion τ D h K (P M u h − u h ) and convection τ C (u h − u h ) parts. In particular, we adapt the technique used in the elasticity problem in [13] and the standard up-winding scheme similar to that in [4,[9][10][11] in the diffusion and convection parts, respectively. It is also worth to mention that we can choose τ C to be any function which satisfies τ C ≥ 1 2 β · n. With the new design of numerical flux (1.3e), we show that the global L 2 -norm of the error of u converges with order k + 2 while that of q converges with order k + 1.…”
Section: Introductionmentioning
confidence: 99%